Comparisons of the oncological results of transoral laser surgery and radiotherapy for early stage laryngeal squamous cell cancer: single-center long-term results - Sumeyra Doluoglu; Omer Bayir; Bulent Ocal; Emel Cadalli Tatar; Mehmet Hakan Korkmaz; Guleser Saylam (Annals of Saudi Medicine, 2024)
BACKGROUND: In the treatment of early stage laryngeal cancers, surgery (transoral laryngeal surgery (TOLS), open partial laryngeal surgery (OPLS) and radiotherapy (RT) are used. OBJECTIVES: Compare the oncological results of patients with early stage laryngeal squamous cell carcinoma (LSCC) treated with TOLS or RT. DESIGN: Retrospective SETTINGS: Tertiary training and research hospital PATIENTS AND METHODS: The participants were divided into patients who underwent TOLS and RT treatment. The groups were compared with each other in terms of local recurrence, regional recurrence, distant metastasis, 3 and 5-year overall survival (OS), disease-free survival (DFS), disease-specific survival (DSS) and laryngectomy-free survival rates (LFS). MAIN OUTCOME MEASURES: The effects of TOLS and RT treatment on local control, regional control, OS, DFS, DDS and LFS in early stage laryngeal cancers. SAMPLE SIZE: 261 RESULTS: The mean follow-up time was 48 (26) months. There were 186 patients who underwent TOLS and 75 patients who underwent RT treatment. Gender, cigarette/alcohol consumption, tumor localization, anterior commissure involvement, tumor grades, recurrence rates and recurrence localizations of the groups were similar. The 5-year overall, disease specific, disease free and laryngectomy-free survival rates were 85.9%, 88%, 79.4%, 96.3% in the TOLS group and 74.3%, 76.7%, 72.3%, 85.2% in the RT group (P=.034, .065, .269, .060, respectively). CONCLUSIONS: TOLS had equal and good oncological outcomes on OS and DFS compared to RT. Anterior commissure involvement was statistically significant independent prognostic risk factor for DFS in both groups. The 5-year OS rate was greater in the TOLS groups (P=.034). LIMITATIONS: Retrospective, but to the best our knowledge, this is the first study in Turkey with a high patient volume and a long follow-up time.